Interpreting the Qur'an : Towards a contemporary approach - Saeed, Abdullah (Routledge, 2006)
this book is about the interpretation of one particular type of Qur'ani texts : the texts that are considered ethico-legal in nature and are represented in the Qur'an's beliefs, rulings, laws , commandements , prohibition God, pro[hets and life after death.